2013
DOI: 10.1112/plms/pdt029
|View full text |Cite
|
Sign up to set email alerts
|

Rational group ring elements with kernels having irrational dimension

Abstract: We prove that there are examples of finitely generated groups Γ together with group ring elements Q ∈ QΓ for which the von Neumann dimension dimLΓ ker Q is irrational, thus (in conjunction with other known results) answering a question of Atiyah. Contents

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 17 publications
0
47
0
Order By: Relevance
“…for any x, y ∈ X. Thus for any ε > max j>k λ j diam( [3,9,12,13,15,25,40] Coornaert and Krieger showed that if a countable amenable group Γ has subgroups of arbitrary large finite index, then for any r ∈ [0, +∞] there is a continuous action of Γ on some compact metrizable space X with mdim(X) = r [8]. Thus it is somehow surprising that the value of the mean dimension of algebraic actions of some amenable groups is rather restricted, as the following consequence of Theorems 1.1 and 8.3 shows: (see also [7] for some related discussion) We shall answer Question 9.1 for algebraic actions of the groups in Theorem 8.3.…”
Section: For a Continuous Action γmentioning
confidence: 99%
“…for any x, y ∈ X. Thus for any ε > max j>k λ j diam( [3,9,12,13,15,25,40] Coornaert and Krieger showed that if a countable amenable group Γ has subgroups of arbitrary large finite index, then for any r ∈ [0, +∞] there is a continuous action of Γ on some compact metrizable space X with mdim(X) = r [8]. Thus it is somehow surprising that the value of the mean dimension of algebraic actions of some amenable groups is rather restricted, as the following consequence of Theorems 1.1 and 8.3 shows: (see also [7] for some related discussion) We shall answer Question 9.1 for algebraic actions of the groups in Theorem 8.3.…”
Section: For a Continuous Action γmentioning
confidence: 99%
“…This was first observed by L. Grabowski and B. Virag in [12,15,26] who used this connection to show that the spectral measure associated with the operator H β of convolution with the element a+a −1 +βc ∈ R[L] is singular continuous. This was achieved through a modification of a method from [1], which appeared in an unpublished work of Grabowski and Virag [15] and for which an exposition appears in the appendix of [13]. The idea is to use an application of the Fourier transform using Pontryagin's dual A = Z/2Z of the base A = Z Z/2Z of the wreath product where {u(n)} n∈Z ∈ 2 (Z) and ω is a sequence of i.i.d random variables taking values in {0, 1} with Bernoulli distribution the assigns probability 1/2 to 0 and 1.…”
Section: The Relation With the Theory Of Random Jacobi And Schrödinger mentioning
confidence: 99%
“…Let {H ω } ω∈Ω be a random ergodic family of Jacobi operators on Z of the form (1) above. An interesting question that is related to this discussion is about the decomposition of the representation π n into irreducible components.…”
Section: Concluding Remarks and Open Problemsmentioning
confidence: 99%
“…Of course, non-integral examples are well-known and can be easily constructed for any group with torsion. Irrational examples were first constructed by T. Austin [4]. Additional examples appear in [8,18].…”
Section: Introductionmentioning
confidence: 99%